Niche derived netrin-1 regulates hematopoietic stem cell dormancy via its receptor neogenin-1 - Renders, Simon; Svendsen, Arthur Flohr; Panten, Jasper; Rama, Nicolas; Maryanovich, Maria; Sommerkamp, Pia; Ladel, Luisa; Redavid, Anna Rita; Gibert, Benjamin; Lazare, Seka; Ducarouge, Benjamin; Schönberger, Katharina; et al. (Nature Communications, 2021)
Haematopoietic stem cells (HSCs) are characterized by their self-renewal potential associated to dormancy. Here we identify the cell surface receptor neogenin-1 as specifically expressed in dormant HSCs. Loss of neogenin-1 initially leads to increased HSC expansion but subsequently to loss of self-renewal and premature exhaustion in vivo. Its ligand netrin-1 induces Egr1 expression and maintains quiescence and function of cultured HSCs in a Neo1 dependent manner. Produced by arteriolar endothelial and periarteriolar stromal cells, conditional netrin-1 deletion in the bone marrow niche reduces HSC numbers, quiescence and self-renewal, while overexpression increases quiescence in vivo. Ageing associated bone marrow remodelling leads to the decline of netrin-1 expression in niches and a compensatory but reversible upregulation of neogenin-1 on HSCs. Our study suggests that niche produced netrin-1 preserves HSC quiescence and self-renewal via neogenin-1 function. Decline of netrin-1 production during ageing leads to the gradual decrease of Neo1 mediated HSC self-renewal.
Gesehen am 22.10.2020